Community Group Empowerment in Parit Tokaya through Local Potential (Pineapple) - Fenny Imelda; Ledy Purwandani; Ichsan Ichsan; M Ali (JPKM (Jurnal Pengabdian Kepada Masyarakat) UNTAN, 2018)
Pineapple is one of the easiest commodities found in Pontianak City. Pineapple has a strategic value related to its content, on the other hand, pineapple is a perishable commodity so that regional diversification needs to be done. In order to synergize the government program in order to realize food security and increase regional economic growth, this Community Service (PPM) activity aims to give a touch of Science and Technology (Science), training and community empowerment. All as an effort to increase the added value of pineapple as a local potential by diversifying to produce culinary made from pineapple, namely candied dried and nata de pina. In pineapple processed training, community groups of Parit Tokaya Urban Village as partners can make dried candied and nata de pina and pack it well. The resulting product is attractive and acceptable organoleptically.